Investment, Internal Funds and Public Banking in Germany - Dirk Engel; Torge Middendorf (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Previous studies argued that low investment-cash flow sensitivities of German firms may be caused by dominance of public banking.The paper addresses this topic and applies a unique accounting dataset of German firms. Results from a dynamic panel data approach show that the dependence of investment spending on internal funds does not significantly differ between firms attached to savings banks, cooperative banks or commercial banks. Thus, the importance of the public banking sector in Germany may not explain the rather low dependence of firms on internal funds and public ownership of borrowers seems not essential to reduce financing constraints.
Keywords: G32; D92; L21; C23; 330; Investment; Relationship Banking; Panel Data; GMM; Investition; Unternehmensfinanzierung; Verschuldungsrestriktion; Cash Flow; Bankensystem; Öffentliche Bank; Schätzung; Deutschland